2018
DOI: 10.1101/378828
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The cap size and shape of Arabidopsis thaliana primary roots impact the root responses to an increase in medium strength

Abstract: During root progression in soil, root cap cells are the first to encounter obstacles. The root cap is known to sense environmental cues, making it a relevant candidate for a mechanosensing site. An original two-layer medium was developed in order to study root responses to growth medium strength and the importance of the root cap in the establishment of these responses. Root growth and trajectory of primary roots of Arabidopsis thaliana seedlings were investigated using in vivo image analysis. After contact wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 32 publications
(50 reference statements)
0
1
0
Order By: Relevance
“…In this context, it has been suggested that touchdependent gravitropic and thigmotropic responses, which include sundry root growth patterns such as root tortuosity/circumnutation function (Taylor et al, 2021), buckling (Silverberg et al, 2012), skewing (Roy and Bassham, 2017), coiling/curling (Lourenco et al, 2015) and waving (Tan et al, 2015), could facilitate root penetration into hard surfaces. At anatomical and morphological levels, a plethora of root specific traits have been reported to be associated with root penetrability such as cortical thickness, stele diameter (Chimungu et al, 2015), root hair density (Bengough et al, 2016), mucilage production (Iijima et al, 2004), sloughing of root cap cells (Bengough and McKenzie, 1997) and root tip geometry (Colombi et al, 2017;Roué et al, 2020). In maize (Zea mays) and wheat (Triticum aestivum), root genotypes with multiseriate cortical sclerenchyma showed greater lignin concentration and bending strength, which in turn, improve their penetration ability in compacted soils (Schneider et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…In this context, it has been suggested that touchdependent gravitropic and thigmotropic responses, which include sundry root growth patterns such as root tortuosity/circumnutation function (Taylor et al, 2021), buckling (Silverberg et al, 2012), skewing (Roy and Bassham, 2017), coiling/curling (Lourenco et al, 2015) and waving (Tan et al, 2015), could facilitate root penetration into hard surfaces. At anatomical and morphological levels, a plethora of root specific traits have been reported to be associated with root penetrability such as cortical thickness, stele diameter (Chimungu et al, 2015), root hair density (Bengough et al, 2016), mucilage production (Iijima et al, 2004), sloughing of root cap cells (Bengough and McKenzie, 1997) and root tip geometry (Colombi et al, 2017;Roué et al, 2020). In maize (Zea mays) and wheat (Triticum aestivum), root genotypes with multiseriate cortical sclerenchyma showed greater lignin concentration and bending strength, which in turn, improve their penetration ability in compacted soils (Schneider et al, 2021).…”
Section: Introductionmentioning
confidence: 99%